Validation of the method of standardization of concomitant impurities in "Carbatryl" tablets - Kucherenko, L. I.; Nimenko, G. R.; Khromylova, O. V.; Кучеренко, Людмила Іванівна; Німенко, Ганна Романівна; Хромильова, Ольга Володимирівна (X. : НФаУ, 2024)
The purpose of our work is to validate the methodology for quantitative determination of accompanying impurities in "Carbatryl" tablets.
Keywords: тези доповідей